Effects of positive reappraisal and self-distancing on the meaningfulness of everyday negative events - Lau, Clement Yong Hao; Tov, William (Frontiers in Psychology, 2023)
Current work on meaning-making has primarily focused on major negative life events such as trauma and loss, leaving common daily adversities unexplored. This study aimed to examine how utilising meaning-making strategies such as positive reappraisal and self-distancing (in isolation or in combination) can facilitate an adaptive processing of these daily negative experiences. Overall meaning and facets of meaning (coherence, purpose, significance/mattering) were assessed at both global and situational levels. Results suggested that positive reappraisal was generally effective for enhancing situational meaning but not under all conditions. Specifically, when negative experiences were high on emotional intensity, reflecting on the experience from a distanced (third-person) perspective enhanced coherence and existential mattering more than engaging in positive reappraisal. However, when negative experiences were low on intensity, distanced reflection led to less coherence and mattering than positive reappraisal. The findings of this study elucidated the importance of examining the multidimensional construct of meaning at its facets and highlighted the importance of applying different coping strategies to effectively make meaning out of daily negative experiences.